Digital adaptation and critical thinking skills in Buddhist religious education at Xaverius 1 junior high school Bandar Lampung - May Tria Agustina; Sutiyono Sutiyono; Juni Suryanadi (International Journal of Science and Applied Science: Conference Series, 2025)
The ability to adapt to technology is not only related to technical skills, but is also believed to be related to cognitive abilities, one of which is critical thinking. The purpose of this study was to determine the effect of digital adaptation on critical thinking skills in Buddhist education at SMP Xaverius 1 Bandar Lampung. This study used a quantitative approach with a survey method involving 50 students as respondents. The research instrument was a questionnaire with a Likert scale that measured digital adaptation abilities with four indicators, namely the ability to use digital technology, the use of technology for learning, digital information evaluation skills, and the ability to adapt to new technology. The success of education is greatly influenced by the quality of learning that can encourage active involvement and deep understanding in students. However, in practice, many students still show low participation, tend to only memorize without being able to analyze the material critically, and misuse technology for activities that do not support the learning process. The lack of interactive teaching methods discourages students from thinking critically or reflecting on the teachings contextually. This study aims to examine the effect of digital adaptation on students' critical thinking skills in Buddhist Education at Xaverius 1 Junior High School in Bandar Lampung. The results of the study show that there is a positive and significant influence between digital adaptation and students' critical thinking skills. The analysis indicates that digital adaptation has a highly significant influence on students’ critical thinking abilities. This finding suggests that the better students adapt to digital technologies, the more capable they become in analyzing, evaluating, and solving problems logically. Overall, digital adaptation plays a strong role in enhancing students’ critical thinking, although other external factors beyond this study also contribute to shaping these skills.